Diásporas Performáticas: impulsos-fluxos (Olhares, 2020)
This article discusses about some artistic interventions, using thehistorical-sociological term “diaspora”, seeking to establish a territory to reflect on the performing art.
Keywords: Diaspora; Performance; Experience; Planet Earth